2018
DOI: 10.1007/s13205-018-1422-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient purification of a recombinant tag-free thermostable Kluyveromyces marxianus uricase by pH-induced self-cleavage of intein and expression in Escherichia coli

Abstract: Uricase as an important healthcare-related protein is extensively used in the treatment of tumor lysis syndrome and in the manufacture of serum uric-acid diagnostic kits. In this study, a gene of a new thermostable uricase (KmUOX) was cloned from thermotolerant yeast . The uricase was fused with a self-cleaving intein and cellulose-binding affinity tag and expressed in BL21 (DE3). Through the binding to inexpensive cellulose and in situ intein cleavage induced by a pH change, tag-free uricase (KmUOX) was effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, urate oxidases appeared to be sensitive to ferrous cation (Fe 2+ ) and ferric cation (Fe 3+ ). The activity of KmUox is completely inhibited by Fe 2+ and Fe 3+ [ 28 ], and we found that the activity of DrUox was apparently inhibited by Fe 2+ and Fe 3+ , with 60% and 80% reduction, respectively. The structural effect of Cu 2+ , Fe 2+ , and Fe 3+ on DrUox did not change protein oligomerization ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, urate oxidases appeared to be sensitive to ferrous cation (Fe 2+ ) and ferric cation (Fe 3+ ). The activity of KmUox is completely inhibited by Fe 2+ and Fe 3+ [ 28 ], and we found that the activity of DrUox was apparently inhibited by Fe 2+ and Fe 3+ , with 60% and 80% reduction, respectively. The structural effect of Cu 2+ , Fe 2+ , and Fe 3+ on DrUox did not change protein oligomerization ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 93%
“…In our study, the Cu 2+ -binding motif was conserved within DrUox and led to 60% loss of enzymatic activity upon preincubation with Cu 2+ , which is similar to urate oxidase from A. globiformis [ 23 ]. Cu 2+ was shown to inactivate C. utilis urate oxidase completely [ 27 ]; however, some reports mentioned that urate oxidases from B. subtilis and K. marxianus (KmUox) were still active in the presence of Cu 2+ despite the lack of a Cu 2+ -binding motif [ 28 , 29 ]. In addition, urate oxidases appeared to be sensitive to ferrous cation (Fe 2+ ) and ferric cation (Fe 3+ ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, a few of urate hydroxylases including BSpucL from B. fastidiosus (Abdelmoneim, 2015), CUpucL from C. utilis (Chen et al, 2008; Liu et al, 2011), AGpucL from A. globiformis (Kiba et al, 2005) and BFpucL from B. subtilis 168 (Li et al, 2017), have been identified and used as commercial uricase for the treatment of gout. In addition, a urate oxidase KMpucL from K. marixianus DMKU3‐1042 also has been reported to be able to convert urate to allantoin (B. Wang et al, 2018). Using the amino acid sequence of CUpucL as a reference, the identity of the urate urate hydroxylases from K. marixianus , B. fastidiosus , A. globiformis , and B. subtilis was 62.7%, 15.7%, 24.4%, 13.7%, respectively (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…In this pathway, urate is generated from hypoxanthine catalyzed by xanthine dehydrogenases. By searching for the literatures and protein database (uniprot), we found that urate can be converted into allantoin by urate oxidases which have been identified from Bacillus fastidiosus (Abdelmoneim, 2015), Candida utilis (Chen et al, 2008; Liu et al, 2011), Kluyveromyces marixianus DMKU3‐1042 (B. Wang et al, 2018), Arthrobacter globiformis (Kiba et al, 2005), and Bacillus subtilis 168 (Li et al, 2017). On this basis, we designed an artificial pathway for allantoin in E. coli by extending its endogenous purine metabolic pathway (Figure 1).…”
Section: Introductionmentioning
confidence: 99%